Экзистенциализм Витольда Гомбровича и Георгия Иванова - Malcew, Leonid (Acta Polono-Ruthenica, 2018)
In the present article a comporative analysis of the novel Ferdidurke by Gombrowich and the story Disintegration of Atom by George Ivanov that were published at the same time and that were interpreted as an artistic realization of the existential ideals is offered. An analysis of philosophic sense of these works is based on aesthetic antinomism of Berdayev who told the difference between an synthetic and an analytic types in modernist art of the XXth century.